Análise técnica e financeira dos sistemas de vedação em Drywall e alvenaria convencional aplicados a um edifício residencial - Anido, Ana Carolina Picinato [UNESP]; Sousa, Priscila Santana de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
A indústria da construção civil é uma das mais importantes para a economia mundial, por outro lado, também se destaca entre as atividades econômicas que mais geram impactos ambientais, devido ao elevado consumo de recursos naturais e geração de resíduos. Neste contexto, este trabalho teve como objetivo analisar comparativamente a viabilidade técnica e financeira do sistema de vedação Drywall com o de alvenaria tradicional em um edifício residencial. Como o Drywall é gerado da reciclagem das sobras de gesso de sistemas construtivos tradicionais, sua utilização tem sido muito incentivada como alternativa para reduzir o consumo de recursos minerais pelo setor de construção civil, além de otimizar o tempo de obra e reduzir os custos com materiais e mão de obra. No presente trabalho foi realizado um estudo de três parâmetros para comparação desses dois sistemas de vedação: método executivo, análise financeira e de produtividade, concluindo que o Drywall gera menos retrabalho e proporciona uma obra mais limpa, além de ser mais econômico e produtivo.

The construction industry is one of the most important for the world economy, on the other hand, it also stands out among the economic activities that generate the most environmental impacts, due to the high consumption of natural resources and waste generation. In this context, this work aims to comparatively analyze the technical and financial viability of the Drywall sealing system with that of traditional masonry in a residential building. As Drywall is generated from the recycling of plaster leftovers from traditional construction systems, its use has been highly encouraged as an alternative to reduce the consumption of mineral resources by the civil construction sector, in addition to optimizing work time and reducing material costs. and manpower. In the present work, a study of three parameters was carried out: comparison of the two financial and productivity management systems, concluding the clean work, in addition to providing a more economical operation, being more economical and productive. In the present work, a study of three parameters was carried out to compare these two sealing systems: executive method, financial and productivity analysis, concluding that Drywall generates less rework and provides a cleaner work, in addition to being more economical and productive.
Technical and financial analysis of drywall and conventional masonry sealing systems applied to a residential building
Keywords: Drywall; Produtividade; Construção sustentável; Gesso; Construção civil; Alvenaria; Civil Construction; Plaster; Sustainable Buildings; Productivity; Construção civil; Sustentabilidade; Vedação (Tecnologia)